Resignifying the gaze from the complex thinking through the aesthetic appreciation of "Melancolía I" - Jiménez Murcia, Ana (2020)
The investigation has allowed to generate a proposal for appreciation of the aesthetic piece "Melancholy I" of Alberto Durero, grounded on the theoretical principles of Edgar Morín, which are related with his conception of Complex Thought, and support the education gaze. To this end, I propose a guide for pedagogical interpretation, which favored the analysis and appreciation of the work mentioned. Concerning the naturalness of the investigation, the method is of hermeneutic qualitative character, by means of a dialogical relation between artist, teachers and contemplators. The results depicted how viewers relate to fundamental elements of grasping and connecting symbols of renaissance with their inner world. Product of this researching, was produced a proposal of interpretation of an aesthetic piece, that contributed to the improvement of the teaching of the art appreciation.